Dimitrie Cantemir: mize ale gândirii filosofice timpurii - Ştefan Afloroaei (Revista de Istorie și Teorie Literară)
The early writings of Cantemir, Sacro-sanctae scientiae indepingibilis imago (The Unportrayable Icon of All-holy Science, 1700), received mostly unfavorable reviews. It was considered obscure, for instance, a simple compilation or a note between his truly relevant writings. Few appreciated the actually philosophical reflection of Cantemir (as did Lucian Blaga). What I would like to argue is that in that writing his authentic metaphysical calling became obvious. The metaphysical or speculative attitude (in the old acceptation of the term) was understood by Cantemir either as orientation of the mind towards the previous, the metaphysical (which, in his words, “is inherently universal”), or as enigmatically and partially knowledge (ut in speculo) of the divine, previously mentioned by Christian scholars. Thus we can explain some hard philosophical ideas in his writings, such as that the truth cannot be but one and the same, that there is an original unity, through the creation, of the existing. Similarly there is the idea that any created thing is inherently natural and lasting, supernatural. In contrast to those that regard only the natural condition of man, Cantemir talks of three images thereof: a theological one, a philosophical one (“metaphysical”) and a naturalistic one (“physical”), the latter being rather frequently encountered in his time. The pages in which he approaches such matters reveal a distinct power of analysis and conceptualization, a really advanced speculative endeavor.